Who are the women having non-institutional deliveries in Brazil and who attends them? An analysis of 13.7 million births, 20182022 - Larissa Adna Neves Silva; Cauane Blumenberg; Aluísio J.D. Barros (Revista Panamericana de Salud Pública)
Objective. To identify groups of women in Brazil more likely to have deliveries outside health facilities and the types of professionals attending these deliveries, and to assess related social determinants. Methods. Data from Brazils Live Birth Information System from 2018 to 2022 were used to investigate non-institutional deliveries by region of residence, ethnicity/skin color, schooling, and maternal age at delivery. Associations between these factors were also assessed. The proportion of births attended by doctors, nurses/midwives, traditional birth attendants, and others was also analyzed, comparing institutional and non-institutional deliveries. Results. The overall prevalence of non-institutional deliveries was 1.0%. Higher proportions were observed in the North region (4.0%), and among Indigenous women (26.3%), adolescent mothers (1.4%), and women with fewer than 4 years of schooling (8.3%). The proportion of non-institutional deliveries was 67.6% among, Indigenous women from the North region with little education. Indigenous women with fewer than 4 years of schooling and who had a non-institutional delivery had the highest proportion of deliveries without a qualified professional (95.2%). Conclusions. Cultural norms and barriers to accessing maternity services, combined with broader social inequalities and organizational challenges faced by Indigenous populations, may contribute to the high proportion of non-institutional deliveries without a skilled attendant observed among these women. Culturally sensitive strategies to expand access to maternity care for and empower Indigenous women are crucial to ensure their and their childrens survival.